Betula nana ring widths - Patrick Sullivan (Arctic Data Center, 2016)
Ring width data for Betula nana shrubs growing near the terminus of the Russell Glacier in western Greenland. Samples were collected in support of Cassandra Gamm's M.S. thesis at the University of Alaska Anchorage. The goal of the measurements was to examine long-term growth trends in relation to changes in climate. Data are available in both .rwl and column (.csv) format.